A Modularized Design for Output Synchronization of LTI Dynamical Networks with Communication Delays. Issue 6 (1st November 2018) - Dan, Hayato; Hatanaka, Takeshi; Shim, Hyungbo
Abstract : In this paper, we address output synchronization for a network of heterogeneous agents with linear time invariant single-input-single-output dynamics in the presence of communication delays. To this end, we present a three-stage modularized design procedure: (i) a parallel feedforward compensator is designed to convert the dynamics to a minimum-phase system with relative degree one, (ii) the resulting system is then transformed into a feedback equivalent to a passive system, and (iii) the agents are interconnected based on a passivity-based output synchronization law. The benefit of the present control scheme is that not only implementation but also the design stage of the controller is distributed, namely the agents do not need to know the entire network structure. The present solution is then shown to achieve output synchronization. We finally demonstrate the present controller through simulation.